2020
DOI: 10.29356/jmcs.v64i4.1246
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Alcohol Production by Conversion of Glycerol Over Supported Iron and Nickel Bimetallic Oxides

Abstract: Abstract. The study of catalysts based on iron, nickel, and iron-nickel oxides (Fe, Ni and FeNi) supported on a commercial mesoporous alumina is presented. The metal oxides were synthesized by the incipient wetness impregnation method. The samples were characterized by XRD, TPR-H2, Raman spectroscopy, XPS and N2 adsorption. The catalytic activity was evaluated in the dehydration-dehydrogenation reaction of glycerol in the gas phase. In the iron oxide and nickel oxide catalysts, the result of TPR-H2 showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the combination of the two metals changed the selectivity towards the AA (90 % GL conversion and 90 % AA selectivity) whereas with the monometallic oxides, 88 % HAc selectivity was reported. [140] The addition of potassium species to α-Fe 2 O 3 yielded a loss of LAS and, in the presence of formic acid, morphology changes of solid were observed with the formation of BAS. [141] Using these catalysts in the dehydration of GL at 623 K, AA was obtained as the main product (40 % yield, Acr 10 %, others 25 %).…”
Section: Ironmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the combination of the two metals changed the selectivity towards the AA (90 % GL conversion and 90 % AA selectivity) whereas with the monometallic oxides, 88 % HAc selectivity was reported. [140] The addition of potassium species to α-Fe 2 O 3 yielded a loss of LAS and, in the presence of formic acid, morphology changes of solid were observed with the formation of BAS. [141] Using these catalysts in the dehydration of GL at 623 K, AA was obtained as the main product (40 % yield, Acr 10 %, others 25 %).…”
Section: Ironmentioning
confidence: 99%
“…The authors observed that, in these bimetallic catalysts, the presence of nickel reduced the iron oxidation state, enhancing the redox properties of the solid. Moreover, the combination of the two metals changed the selectivity towards the AA (90 % GL conversion and 90 % AA selectivity) whereas with the monometallic oxides, 88 % HAc selectivity was reported [140] . The addition of potassium species to α‐Fe 2 O 3 yielded a loss of LAS and, in the presence of formic acid, morphology changes of solid were observed with the formation of BAS [141] .…”
Section: Late Transition Metalsmentioning
confidence: 99%
See 2 more Smart Citations